النظام القانوني لتأسيس الشركات - ويداد عباد; ابتسام صيد (My University, 2019)
Summary: Companies are subject to the same conditions under which all companies are incorporated, namely, substantive conditions and formal conditions, which result from their breach of contract invalidity so that the type of invalidity varies according to the lagging element s contract, but given the particular nature of the company's contract, this rule cannot be applied in an absolute manner which gave rise to the company's actual theory, Civil companies have forms that distinguish them from commercial companies as the civil company's activity is related to business The company's activities are linked to the field of commerce and industry. Commercial companies are divided into persons, money companies and mixed-nature companies, which are subject to the conditions under which the company is generally founded, otherwise specific provisions for commercial companies regulated under commercial law. ...................... ملخص : تخضع الشركات للنفس الشروط التي تتأسس بها كافة الشركات وهي الشروط الموضوعية والشروط الشكلية والتي يترتب عن مخالفتها بطلان العقد بحيث يختلف نوع البطلان بحسب الركن المتخلف، فقد يكون بطلانا مطلقا أو نسبيا أو من نوع خاص والقاعدة العامة تقضي بزوال العقد لكن نظرا للطبيعة الخاصة لعقد الشركة لا يمكن تطبيق هذه القاعدة بصفة مطلقة والذي أدى إلى ظهور نظرية الشركة الفعلية ،وللشركات المدنية أشكالا تميزها عن الشركات التجارية إذ يرتبط نشاط الشركة المدنية بالأعمال المدنية أما الشركة التجارية فنشاطها مرتبط بمجال التجارة والصناعة . وتنقسم الشركات التجارية إلى شركات أشخاص وشركات أموال وشركات ذات طبيعة مختلطة تخضع في تأسيسها إلى الشروط التي تتأسس بها الشركة بوجه عام وإلا أحكام خاصة بالشركات التجارية المنظمة بموجب القانون التجاري . ......................... Résumé : Les sociétés sont soumises aux mêmes conditions que toutes les sociétés, c’est-à-dire les conditions de fond et les conditions de forme qui résultent de la violation de la nullité du contrat, de sorte que le type de nullité varie en fonction de l’épine dorsale: nul ou non, ou un type spécial. Cette règle ne peut pas être appliquée de manière absolue, ce qui a conduit à l’émergence de la théorie de la société actuelle. Les sociétés civiles les distinguent des sociétés commerciales, car l’activité de la société civile est associée aux travaux de génie civil et aux activités de la société liées au secteur du commerce et de l’industrie. Les sociétés commerciales sont divisées en sociétés, sociétés, fonds et sociétés de nature mixte, soumises aux conditions dans lesquelles la société est créée en général, et uniquement aux dispositions de sociétés commerciales organisées en vertu du droit commercial.